Fibrous carbon nanostructure, method for producing fibrous carbon nanostructure, and method for producing surface-modified fibrous carbon nanostructure
Patent Information
- Application Number
- JP2021508989
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-27
- Filing Date
- 2020-03-10
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-03-10
AI Technical Summary
【0016】 本発明によれば、表面改質処理し易い繊維状炭素ナノ構造体およびその製造方法を提供することができる。 また、本発明によれば、良好に表面改質処理された表面改質繊維状炭素ナノ構造体の製造方法を提供することができる。
Smart Images

Figure 0007632275000002 
Figure 0007632275000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a fibrous carbon nanostructure, a method for producing a fibrous carbon nanostructure, and a method for producing a surface-modified fibrous carbon nanostructure. [Background technology]
[0002] In recent years, fibrous carbon nanostructures such as carbon nanotubes (hereinafter sometimes referred to as "CNTs") have been attracting attention as materials with excellent electrical conductivity, thermal conductivity and mechanical properties.
[0003] However, fibrous carbon nanostructures such as CNTs tend to form bundle structures due to van der Waals forces and are difficult to disperse in solvents or resins, making it difficult to achieve the desired high properties.
[0004] In view of this, a technique has been proposed for improving the dispersibility of fibrous carbon nanostructures such as CNTs by subjecting the fibrous carbon nanostructures to a surface modification treatment such as an oxidation treatment (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2015 / 045418 Summary of the Invention [Problem to be solved by the invention]
[0006] Here, from the viewpoint of obtaining surface-modified fibrous carbon nanostructures with excellent dispersibility by surface modification treatment of the fibrous carbon nanostructures, it is necessary to perform a good surface modification treatment on the raw material fibrous carbon nanostructures.
[0007] However, conventional fibrous carbon nanostructures have room for improvement in terms of the ease with which they can be subjected to surface modification treatment.
[0008] Therefore, an object of the present invention is to provide a fibrous carbon nanostructure that is easy to subject to surface modification treatment, and a method for producing the same. Another object of the present invention is to provide a surface-modified fibrous carbon nanostructure which has been subjected to a satisfactory surface modification treatment. [Means for solving the problem]
[0009] The present inventors have conducted extensive research in order to achieve the above object, and have found that fibrous carbon nanostructures having predetermined properties are easily surface-modified, thereby completing the present invention.
[0010] That is, the present invention aims to advantageously solve the above-mentioned problems, and the fibrous carbon nanostructure of the present invention is characterized in that the half-width of the peak of a temperature differential curve, which is a first-order differential curve of a thermogravimetric curve obtained by thermogravimetric analysis in a dry air atmosphere (hereinafter, the "temperature differential curve, which is a first-order differential curve of a thermogravimetric curve" will be simply referred to as the "temperature differential curve") is 38°C or more and less than 90°C, and the high-temperature side temperature at 1 / 10 of the peak top height of the peak is 658°C or more. A fibrous carbon nanostructure having a half-width of the peak of a temperature differential curve of 38°C or more and less than 90°C, and a high-temperature side temperature at 1 / 10 of the peak top height of the peak is 658°C or more, is easily surface-modified when subjected to a surface modification treatment such as an oxidation treatment. In the present invention, the term "peak" refers to a point where the absolute value of the weight change rate per 1°C is maximum in a convex curve portion including a point where the absolute value of the weight change rate per 1°C is maximum in a temperature derivative curve (e.g., FIG. 1) (e.g., DTG in FIG. 1). max ), and the lower temperature (for example, T ini) and the higher temperature. However, the point at which the absolute value of the weight change rate per 1°C is a minimum value (the minimum value when there is only one mountain (maximum value) and no minimum value as in FIG. 1) is 1 / 10 or less of the peak top height of the peak. In addition, the "half width of the peak" and the "higher temperature at a height 1 / 10 of the peak top height of the peak" can be determined using the method described in the Examples of this specification.
[0011] In addition, the fibrous carbon nanostructure of the present invention preferably has a weight loss rate of 40% or less at a lower temperature at a height that is 7.5 / 10 of the peak top height of the peak. A fibrous carbon nanostructure having a weight loss rate of 40% or less at a lower temperature at a height that is 7.5 / 10 of the peak top height of the peak is more likely to be surface-modified when subjected to a surface modification treatment such as an oxidation treatment. In the present invention, the "weight loss rate at a lower temperature at a height that is 7.5 / 10 of the peak top height of the peak" can be determined by the method described in the Examples of this specification.
[0012] In the fibrous carbon nanostructure of the present invention, the peak top temperature is preferably 530° C. or higher and lower than 730° C. A fibrous carbon nanostructure having a peak top temperature lower than 530° C. is easily burned away when subjected to a surface treatment modification such as oxidation treatment, whereas a fibrous carbon nanostructure having a peak top temperature of 730° C. or higher is less likely to be surface-modified when subjected to a surface treatment modification such as oxidation treatment. In the present invention, the "peak top temperature of the peak" can be determined by the method described in the Examples of this specification.
[0013] The present invention also aims to advantageously solve the above-mentioned problems, and the method for producing a fibrous carbon nanostructure of the present invention is a method for producing a fibrous carbon nanostructure for producing any of the above-mentioned fibrous carbon nanostructures, and is characterized in that it includes a step of heating the fibrous carbon nanostructure to a temperature of 120°C or higher under a vacuum atmosphere.
[0014] The present invention aims to advantageously solve the above-mentioned problems, and the method for producing a fibrous carbon nanostructure of the present invention is a method for producing a fibrous carbon nanostructure for producing any of the above-mentioned fibrous carbon nanostructures, and is characterized in that it includes a step of heating the fibrous carbon nanostructure to a temperature of 800°C or higher under an inert gas atmosphere.
[0015] The present invention also provides a method for producing a surface-modified fibrous carbon nanostructure, comprising the steps of: subjecting any one of the above-mentioned fibrous carbon nanostructures to a surface modification treatment to obtain a surface-modified fibrous carbon nanostructure, wherein the surface modification treatment may be a wet oxidation treatment. Effect of the Invention
[0016] According to the present invention, it is possible to provide a fibrous carbon nanostructure that is easy to subject to surface modification treatment and a method for producing the same. Furthermore, according to the present invention, it is possible to provide a method for producing a surface-modified fibrous carbon nanostructure which has been satisfactorily surface-modified. [Brief description of the drawings]
[0017] [Figure 1] 1 is a graph showing a schematic shape of a peak of a temperature differential curve. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, an embodiment of the present invention will be described in detail. Here, the fibrous carbon nanostructure of the present invention is easily surface-modified when subjected to a surface modification treatment such as an oxidation treatment, etc. The surface-modified fibrous carbon nanostructure obtained by subjecting the fibrous carbon nanostructure of the present invention to a surface modification treatment is not particularly limited, and can be suitably used, for example, when preparing a dispersion liquid in which the surface-modified fibrous carbon nanostructure is dispersed in a dispersion medium.
[0019] (fibrous carbon nanostructures) The fibrous carbon nanostructure of the present invention requires that the half-width of the peak in the temperature differential curve obtained by thermogravimetric analysis in a dry air atmosphere is 38° C. or more and less than 90° C., and that the high-temperature side temperature at 1 / 10 of the peak top height of the peak is 658° C. or more. Since the half-width of the peak in the temperature differential curve of the present invention is 38° C. or more and less than 90° C., and the high-temperature side temperature at 1 / 10 of the peak top height of the peak is 658° C. or more, the fibrous carbon nanostructure of the present invention is well surface-modified when subjected to a surface modification treatment such as an oxidation treatment.
[0020] Here, the fibrous carbon nanostructure is not particularly limited, and examples thereof include cylindrical carbon nanostructures such as carbon nanotubes (CNTs) and non-cylindrical carbon nanostructures such as carbon nanostructures in which a six-membered carbon ring network is formed into a flattened cylinder. The fibrous carbon nanostructure of the present invention may contain one kind of the above-mentioned carbon nanostructure alone, or may contain two or more kinds of them.
[0021] Among the above, the fibrous carbon nanostructure is preferably a fibrous carbon nanostructure containing CNT, because the fibrous carbon nanostructure containing CNT can exhibit particularly excellent properties (e.g., electrical conductivity, thermal conductivity, strength, etc.) when the dispersibility is increased by a surface modification treatment.
[0022] The fibrous carbon nanostructure containing CNT may be composed only of CNT, or may be a mixture of CNT and a fibrous carbon nanostructure other than CNT. The CNT in the fibrous carbon nanostructure is not particularly limited, and single-walled carbon nanotubes and / or multi-walled carbon nanotubes can be used, but the CNT is preferably a single-walled to five-walled carbon nanotube, and more preferably a single-walled carbon nanotube, because the fewer the number of walls of the carbon nanotube, the more excellent the properties can be exhibited when the dispersibility is increased by surface modification treatment.
[0023] Here, the fibrous carbon nanostructure of the present invention must have a half-width of the peak of the temperature differential curve obtained by thermogravimetric analysis in a dry air atmosphere of 38° C. or more and less than 90° C., and the half-width of the peak of the temperature differential curve of the fibrous carbon nanostructure is preferably 40° C. or more, and more preferably 49° C. or less. The half-width of the peak of the temperature differential curve of the fibrous carbon nanostructure is preferably 85° C. or less, and more preferably 80° C. or less. If the half-width of the peak of the temperature differential curve is equal to or more than the lower limit of the preferred range, impurities that promote air oxidation can be removed, and if the half-width of the peak of the temperature differential curve is equal to or less than the upper limit of the preferred range, burning off during surface modification of the fibrous carbon nanostructure can be suppressed.
[0024] Furthermore, the fibrous carbon nanostructure of the present invention must have a high-temperature side temperature at 1 / 10 the peak top height of the peak of the temperature differential curve obtained by thermogravimetric analysis in a dry air atmosphere of 658° C. or more, and the high-temperature side temperature at 1 / 10 the peak top height of the peak of the temperature differential curve of the fibrous carbon nanostructure is preferably 660° C. or more, more preferably 665° C. or more, even more preferably 673° C. or more, even more preferably 689° C. or more, and is usually 760° C. or less. If the high-temperature side temperature at 1 / 10 the peak top height of the peak of the temperature differential curve is equal to or higher than the lower limit of the preferred range, the surface is more satisfactorily modified when a surface modification treatment such as an oxidation treatment is performed.
[0025] Furthermore, the fibrous carbon nanostructure of the present invention preferably has a weight loss rate at a lower temperature at 7.5 / 10 of the peak top height of the peak of a temperature differential curve obtained by thermogravimetric analysis in a dry air atmosphere of 40% by weight or less, more preferably 38% by weight or less, even more preferably 35% by weight or less, even more preferably 31% by weight or less, even more preferably 29% by weight or less, and usually 10% by weight or more. When the weight loss rate at a lower temperature at 7.5 / 10 of the peak top height of the peak of a temperature differential curve is less than the above upper limit, the surface is more satisfactorily modified when subjected to a surface modification treatment such as an oxidation treatment.
[0026] Furthermore, the fibrous carbon nanostructure of the present invention preferably has a peak top temperature of a peak in a temperature differential curve obtained by thermogravimetric analysis in a dry air atmosphere of 530° C. or more, more preferably 550° C. or more, and even more preferably 570° C. or more, and preferably less than 730° C., more preferably 710° C. or less, and even more preferably 690° C. or less. When the peak top temperature of the peak in the temperature differential curve is 530° C. or more and less than 730° C., the surface is more satisfactorily modified when a surface modification treatment such as an oxidation treatment is performed.
[0027] A thermogravimetric curve is a curve with mass on the vertical axis and temperature on the horizontal axis, and a first derivative curve of a thermogravimetric curve is a temperature derivative curve with differential thermogravimetry (DTG) on the vertical axis and temperature on the horizontal axis.
[0028] Furthermore, (i) the half-width (°C), (ii) the higher temperature at 1 / 10 of the peak top height ("b value" in Table 1) (°C), (iii) the weight loss rate (weight %) at the lower temperature at 7.5 / 10 of the peak top height of the peak of the temperature differential curve of the fibrous carbon nanostructure, and (iv) the peak top temperature (°C) can be adjusted by changing the pretreatment conditions of the fibrous carbon nanostructure (e.g., the atmosphere during pretreatment (vacuum atmosphere or inert gas atmosphere) and the treatment temperature, etc.).
[0029] The average diameter of the fibrous carbon nanostructure is preferably 1 nm or more, more preferably 60 nm or less, more preferably 30 nm or less, and even more preferably 10 nm or less. The fibrous carbon nanostructure having an average diameter within the above range can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment. Here, in the present invention, the "average diameter of fibrous carbon nanostructures" can be determined by measuring the diameter (outer diameter) of, for example, 20 randomly selected fibrous carbon nanostructures on a transmission electron microscope (TEM) image and calculating the number average value.
[0030] As the fibrous carbon nanostructure, it is preferable to use a fibrous carbon nanostructure having a ratio (3σ / Av) of the standard deviation of the diameter (σ: sample standard deviation) multiplied by 3 to the average diameter (Av) of more than 0.20 and less than 0.80, more preferably a fibrous carbon nanostructure having a 3σ / Av of more than 0.25, and even more preferably a fibrous carbon nanostructure having a 3σ / Av of more than 0.50. Fibrous carbon nanostructures having a 3σ / Av of more than 0.20 and less than 0.80 can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment. The average diameter (Av) and standard deviation (σ) of the fibrous carbon nanostructures may be adjusted by changing the manufacturing method or manufacturing conditions of the fibrous carbon nanostructures, or by combining multiple types of fibrous carbon nanostructures obtained by different manufacturing methods.
[0031] Furthermore, the average length of the fibrous carbon nanostructure is preferably 10 μm or more, more preferably 50 μm or more, and even more preferably 80 μm or more, and is preferably 600 μm or less, more preferably 550 μm or less, and even more preferably 500 μm or less. The fibrous carbon nanostructure having an average length within the above range can exhibit particularly excellent properties when its dispersibility is enhanced by a surface modification treatment. In the present invention, the "average length of fibrous carbon nanostructures" can be determined by measuring the lengths of, for example, 20 fibrous carbon nanostructures on a scanning electron microscope (SEM) image and calculating the number-average value.
[0032] Here, the fibrous carbon nanostructure usually has an aspect ratio of more than 10. The aspect ratio of the fibrous carbon nanostructure can be determined by measuring the diameter and length of 20 randomly selected fibrous carbon nanostructures using a scanning electron microscope or a transmission electron microscope and calculating the average value of the ratio of the diameter to the length (length / diameter).
[0033] In addition, the fibrous carbon nanostructure has a BET specific surface area of 600 m 2 / g or more, and 2 / g or more is more preferable, and 2000m 2 / g or less, and 2 / g or less is more preferable, and 1600m 2 It is more preferable that the BET specific surface area of the fibrous carbon nanostructure is 600 m 2 When the BET specific surface area of the fibrous carbon nanostructure is 2000 m / g or more, it can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment. 2 If the molecular weight is 1.0 to 1.0 g, the dispersibility can be sufficiently increased when the surface is modified. In the present invention, the term "BET specific surface area" refers to a nitrogen adsorption specific surface area measured by the BET method.
[0034] In addition, it is preferable that the fibrous carbon nanostructure is not subjected to an aperture treatment and that the t-plot obtained from the adsorption isotherm shows an upwardly convex shape. The fibrous carbon nanostructure showing the upwardly convex t-plot can exhibit particularly excellent properties when the dispersibility is enhanced by a surface modification treatment. The "t-plot" can be obtained by converting the relative pressure into the average thickness t (nm) of the nitrogen gas adsorption layer in the adsorption isotherm of the fibrous carbon nanostructure measured by the nitrogen gas adsorption method. That is, the t-plot of the fibrous carbon nanostructure can be obtained by determining the average thickness t of the nitrogen gas adsorption layer corresponding to the relative pressure from a known standard isotherm in which the average thickness t of the nitrogen gas adsorption layer is plotted against the relative pressure P / P0, and performing the above conversion (t-plot method by de Boer et al.). In this specification, the "t-plot" can be determined using the method described in the Examples of this specification.
[0035] Here, in a material having pores on the surface, the growth of a nitrogen gas adsorption layer is classified into the following processes (1) to (3). The slope of the t-plot changes depending on the processes (1) to (3) below. (1) The process of forming a monolayer of nitrogen molecules on the entire surface (2) Formation of multilayer adsorption and the associated capillary condensation filling process in the pores (3) The formation of multilayer adsorption on an apparently non-porous surface whose pores are filled with nitrogen
[0036] In the t-plot showing an upward convex shape, the plot is located on a straight line passing through the origin in the region where the average thickness t of the nitrogen gas adsorption layer is small, whereas as t increases, the plot shifts downward from the straight line. Fibrous carbon nanostructures having such a t-plot shape have a large ratio of the internal specific surface area to the total specific surface area of the fibrous carbon nanostructure, indicating that a large number of openings are formed in the carbon nanostructures that make up the fibrous carbon nanostructure.
[0037] The inflection point of the t-plot of the fibrous carbon nanostructure is preferably in the range of 0.2≦t(nm)≦1.5, more preferably in the range of 0.45≦t(nm)≦1.5, and even more preferably in the range of 0.55≦t(nm)≦1.0. If the inflection point of the t-plot of the fibrous carbon nanostructure is in this range, it can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment. The "position of the bending point" is the intersection of the approximation line A in the above-mentioned process (1) and the approximation line B in the above-mentioned process (3).
[0038] Furthermore, the fibrous carbon nanostructure preferably has a ratio (S2 / S1) of the internal specific surface area S2 to the total specific surface area S1 obtained from a t-plot of 0.05 to 0.30. If the S2 / S1 value of the fibrous carbon nanostructure is within this range, it can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment. Here, the total specific surface area S1 and the internal specific surface area S2 of the fibrous carbon nanostructure can be obtained from the t-plot. Specifically, first, the total specific surface area S1 can be obtained from the slope of the approximation line in step (1), and the external specific surface area S3 can be obtained from the slope of the approximation line in step (3). Then, the internal specific surface area S2 can be calculated by subtracting the external specific surface area S3 from the total specific surface area S1.
[0039] Incidentally, the measurement of the adsorption isotherm of the fibrous carbon nanostructure, the creation of t-plots, and the calculation of the total specific surface area S1 and the internal specific surface area S2 based on the analysis of the t-plots can be performed, for example, using a commercially available measuring device, "BELSORP (registered trademark)-mini" (manufactured by BEL Japan Co., Ltd.).
[0040] Furthermore, the fibrous carbon nanostructure containing CNTs suitable for the fibrous carbon nanostructure preferably has a radial breathing mode (RBM) peak when evaluated by Raman spectroscopy. Note that the Raman spectrum of a fibrous carbon nanostructure consisting only of multi-walled carbon nanotubes having three or more walls does not have an RBM.
[0041] In addition, the fibrous carbon nanostructure containing CNTs preferably has a ratio of G band peak intensity to D band peak intensity in a Raman spectrum (G / D ratio) of 0.5 to 5.0. If the G / D ratio is 0.5 to 5.0, the nanostructure can exhibit particularly excellent properties when the dispersibility is increased by a surface modification treatment. In addition, in this specification, the "G / D ratio" can be determined using the following method. <G / D ratio> Using a microscopic Raman system (Nicolet Almega XR, manufactured by Thermo Fisher Scientific Co., Ltd.), measurement is performed on the fibrous carbon nanostructure near the center of the substrate.
[0042] And the carbon purity of the fibrous carbon nanostructure is preferably 98% by mass or more, more preferably 99% by mass or more, and even more preferably 99.9% by mass or more. In addition, in this specification, the "carbon purity" can be determined using the following method. <carbon purity> Using a thermogravimetric analyzer (TG), the carbon purity (=(weight reduced by combustion until reaching 800°C / initial weight) × 100 (%)) is determined from the weight reduction when the fibrous carbon nanostructure is heated to 800°C in air.
[0043] <Pretreatment> The pretreatment may include (i) a step of heating the fibrous carbon nanostructure at a temperature of 120°C or higher, preferably 190°C or higher (usually 300°C or lower) in a vacuum atmosphere, or (ii) a step of heating the fibrous carbon nanostructure at a temperature of 800°C or higher, preferably 900°C or higher (usually 1,100°C or lower) in an inert gas atmosphere, but it is preferably included a step of heating under vacuum. By setting the treatment temperature to a temperature equal to or higher than the lower limit, it is easier to be surface-modified when a surface modification treatment such as an oxidation treatment is performed, and by setting the treatment temperature to a temperature equal to or lower than the upper limit, the loss of the fibrous carbon nanostructure can be suppressed. Examples of the inert gas preferably include nitrogen, argon, helium, and the like. In addition, the above-mentioned (i) step of heating the fibrous carbon nanostructure to 120°C or higher in a vacuum atmosphere may be performed after the above-mentioned (ii) step of heating the fibrous carbon nanostructure to 800°C or higher in an inert gas atmosphere, or the above-mentioned (ii) step of heating the fibrous carbon nanostructure to 800°C or higher in an inert gas atmosphere may be performed after the above-mentioned (i) step of heating the fibrous carbon nanostructure to 120°C or higher in a vacuum atmosphere.
[0044] The pretreatment time is preferably 10 minutes or more, more preferably 1 hour or more, and even more preferably 3 hours or more, and is preferably 36 hours or less, more preferably 30 hours or less, and even more preferably 24 hours or less. By setting the treatment time to the lower limit or more, impurities that promote air oxidation can be removed, and by setting the treatment time to the upper limit or less, burning down of the fibrous carbon nanostructures can be suppressed.
[0045] (Method for producing surface-modified fibrous carbon nanostructures) In the method for producing a surface-modified fibrous carbon nanostructure of the present invention, a surface-modified fibrous carbon nanostructure having the above-mentioned predetermined properties is subjected to a surface modification treatment to obtain a surface-modified fibrous carbon nanostructure.
[0046] <Surface modification treatment> The surface modification treatment is not particularly limited, and can be carried out using a surface modification treatment agent such as nitric acid, sulfuric acid, a mixed acid of nitric acid and sulfuric acid, ozone, fluorine gas, or hydrogen peroxide. Among them, from the viewpoint of obtaining a surface-modified fibrous carbon nanostructure having excellent dispersibility, the surface modification treatment is preferably a wet oxidation treatment carried out using nitric acid, sulfuric acid, or a mixed acid of nitric acid and sulfuric acid, and more preferably a wet oxidation treatment carried out using a mixed acid of nitric acid and sulfuric acid. In addition, the surface modification treatment conditions can be set according to the type of surface modification treatment agent used and the desired properties of the surface-modified fibrous carbon nanostructure.
[0047] <Surface-modified fibrous carbon nanostructures> The surface-modified fibrous carbon nanostructure obtained by subjecting the fibrous carbon nanostructure of the present invention to surface modification treatment can be well dispersed in a dispersion medium such as water, without particular limitation, without the use of a dispersant. The obtained fibrous carbon nanostructure dispersion can be used to manufacture various molded products (e.g., antistatic films, transparent conductive films, etc.). EXAMPLES
[0048] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following, "%" representing an amount is based on mass unless otherwise specified.
[0049] In the examples and comparative examples, (I) (i) half-width (°C) of the peak in the temperature differential curve, (ii) higher temperature (b value) (°C) at 1 / 10 of the peak top height, (iii) weight loss rate (wt%) at the lower temperature at 7.5 / 10 of the peak top height, and (iv) peak top temperature (°C) of the fibrous carbon nanostructure containing CNT, as well as (II) surface modification processability were measured or evaluated using the following methods.
[0050] <Temperature differential curve> Using a thermogravimetric and differential thermal simultaneous measurement apparatus (manufactured by BrukerAXS, product name "TG-DTA2020SA"), 2.00 mg of the measurement sample was placed on the Pt pan (100 μL) of the thermogravimetric and differential thermal simultaneous measurement apparatus, and the thermogravimetric curve of the fibrous carbon nanostructure was measured under conditions of a heating rate of 5°C / min and a dry air flow rate of 200 mL / min (data acquisition frequency: 0.5 seconds / point), and a temperature differential curve, which is a first differential curve (first differential curve creation conditions: differential width 10 points), was obtained. Here, in the thermogravimetry curve, the vertical axis represents mass and the horizontal axis represents temperature, and in the temperature differential curve, as shown in FIG. 1, for example, the vertical axis represents differential thermogravimetry (DTG) and the horizontal axis represents temperature. In FIG. 1, the peaks indicated by solid lines are those before pretreatment (eg, Comparative Examples 1 to 4), and the peaks indicated by dashed lines are those after pretreatment (eg, Examples 1 to 4). Then, from the peak of the temperature differential curve, (i) the half-width (°C), (ii) the higher temperature (b value) (°C) at a height that is 1 / 10 of the peak top height, (iii) the weight loss rate (wt%) at the lower temperature at a height that is 7.5 / 10 of the peak top height, and (iv) the peak top temperature (°C) were determined. (i) Half-width (℃): T b -T a (ii) High-temperature side temperature (°C) at 1 / 10 of the peak top height (h / 10) (the "b value" in Table 1): T c (iii) The lower temperature T at 7.5 / 10 of the peak top height h (7.5h / 10) d Weight loss rate (wt%) in ("Weight loss rate" in Table 1): A (iv) Peak top temperature (°C): T max T max : Peak top temperature (℃) DTG max :Temperature T max Differential thermogravimetry at (% / ℃) (peak top height h) T ini : Peak start temperature (℃) T a : Differential thermogravimetry value is DTG max Temperature (℃) at which the temperature becomes 1 / 2 (h / 2) (low temperature side) T b : Differential thermogravimetry value is DTG max Temperature (℃) at which the temperature becomes 1 / 2 (h / 2) of the b >T a ) T c : Differential thermogravimetry value is DTG max Temperature (℃) at which the temperature becomes 1 / 10 (h / 10) (high temperature side) T d : Differential thermogravimetry value is DTG max Temperature (℃) at which the temperature becomes 7.5 / 10 (7.5h / 10) (low temperature side) A:T ini From T d Peak area (peak integral value) in the temperature range up to <Surface modification processability> 0.80 g of the obtained fibrous carbon nanostructure (Examples 1 to 4: after pretreatment, Comparative Examples 1 to 4: without pretreatment), 54.8 g of ion-exchanged water, and 83 mL of a mixed acid solution containing sulfuric acid (manufactured by Wako Pure Chemical Industries, Ltd., concentration 96 to 98%) and nitric acid (manufactured by Wako Pure Chemical Industries, Ltd., concentration 69 to 70%) in a 1:3 (volume ratio) ratio were added to a 300 mL flask equipped with a cooling tube and stirring blade, and the mixture was then heated with stirring at an internal temperature of 110°C for 8 hours. 3.0 g of the resulting fibrous carbon nanostructure / mixed acid solution after the mixed acid treatment (sometimes called "main treatment" or "wet oxidation treatment") was weighed into a 50 mL sample bottle and diluted with 27.0 g of ion-exchanged water. After removing the supernatant, ion-exchanged water was added to make the liquid volume 30 mL. After adding 0.1% ammonia water to adjust the pH to 7.0, ultrasonic irradiation was performed at a frequency of 42 Hz for 50 minutes using an ultrasonic irradiation device (manufactured by Branson, product name "BRANSON5510") to obtain a dispersion of fibrous carbon nanostructures. [Evaluation of dispersion liquid] The obtained dispersion was centrifuged for 40 minutes at 20,000G using a centrifuge (manufactured by Beckman Coulter, product name "OPTIMA XL100K") and the supernatant was collected. This cycle was repeated three times to obtain 20 mL of a dispersion of fibrous carbon nanostructures after centrifugation. The obtained dispersion was visually inspected for the presence or absence of aggregates. In addition, a spectrophotometer (manufactured by JASCO, product name "V670") was used to measure the absorbance Ab1 (light path length 1 cm, wavelength 550 nm) of the dispersion before processing with a centrifuge, and the absorbance Ab2 (light path length 1 cm, wavelength 550 nm) of the dispersion after processing with a centrifuge. The dispersibility of the fibrous carbon nanostructures was evaluated by calculating the rate of decrease in absorbance due to centrifugation processing using the following formula. The smaller the rate of decrease in absorbance (50% or less), the better the surface modification of the fibrous carbon nanostructures and the better the dispersibility of the fibrous carbon nanostructures. Absorbance reduction rate (%)={1-(Ab2 / Ab1)}×100 [Evaluation of molded products (films)] The obtained dispersion was applied to a glass substrate using a bar coater #2 and then dried at 130° C. for 10 minutes to form a film made of fibrous carbon nanostructures on the glass substrate. The obtained film was observed under an optical microscope (magnification 100x) to confirm the presence or absence of agglomerates (diameter 30 μm or more) of the fibrous carbon nanostructures visible in the field of view of the microscope, thereby evaluating the dispersibility of the fibrous carbon nanostructures. The fewer the number of agglomerates of the fibrous carbon nanostructures, the better the surface modification of the fibrous carbon nanostructures is, indicating that the dispersibility of the fibrous carbon nanostructures is excellent. 〔comprehensive evaluation〕 A case in which the absorbance decrease rate was 50% or less, there were no aggregates in the dispersion liquid, and there were no aggregate lumps in the film was rated "excellent," and cases other than "excellent" were rated "unacceptable."
[0051] Example 1 As an oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs), we used single-walled carbon nanotubes, "ZEONANO SG101" manufactured by Zeon Nanotechnology Co., Ltd. This fibrous carbon nanostructure containing CNTs was pretreated by heating it at 190°C for 15 hours under vacuum using an oven equipped with an oil rotary vacuum pump. The obtained fibrous carbon nanostructures were evaluated for (I) the (i) half-width (°C) of the peak in the temperature differential curve, (ii) the higher temperature (b value) (°C) at 1 / 10 of the peak top height, (iii) the weight loss rate (wt%) at the lower temperature at 7.5 / 10 of the peak top height, (iv) the peak top temperature (°C), and (II) surface modification processability. The results are shown in Table 1.
[0052] Example 2 An oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs) was obtained in the same manner as in Example 1, except that instead of performing a pretreatment of heating at 190°C under vacuum for 15 hours, a pretreatment of heating at 120°C under vacuum for 15 hours was performed. The obtained fibrous carbon nanostructures were evaluated for (I) the (i) half-width (°C) of the peak in the temperature differential curve, (ii) the higher temperature (b value) (°C) at 1 / 10 of the peak top height, (iii) the weight loss rate (wt%) at the lower temperature at 7.5 / 10 of the peak top height, (iv) the peak top temperature (°C), and (II) surface modification processability. The results are shown in Table 1.
[0053] Example 3 An oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs) was obtained in the same manner as in Example 1, except that instead of performing a pretreatment of heating at 190°C for 15 hours under a vacuum, a pretreatment of heating at 900°C for 6 hours under a nitrogen atmosphere was performed. The obtained fibrous carbon nanostructures were evaluated for (I) the (i) half-width (°C) of the peak in the temperature differential curve, (ii) the higher temperature (b value) (°C) at 1 / 10 of the peak top height, (iii) the weight loss rate (wt%) at the lower temperature at 7.5 / 10 of the peak top height, (iv) the peak top temperature (°C), and (II) surface modification processability. The results are shown in Table 1.
[0054] Example 4 An oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs) was obtained in the same manner as in Example 1, except that instead of performing a pretreatment of heating at 190°C for 15 hours under a vacuum, a pretreatment of heating at 800°C for 6 hours under a nitrogen atmosphere was performed. The obtained fibrous carbon nanostructures were evaluated for (I) the (i) half-width (°C) of the peak in the temperature differential curve, (ii) the higher temperature (b value) (°C) at 1 / 10 of the peak top height, (iii) the weight loss rate (wt%) at the lower temperature at 7.5 / 10 of the peak top height, (iv) the peak top temperature (°C), and (II) surface modification processability. The results are shown in Table 1.
[0055] Comparative Example 1 Zeon Nano Technology's "ZEONANO SG101" is a single-walled carbon nanotube as an oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs) that has not been pretreated by heating under vacuum. (I) (i) half-width (℃) of the peak in the temperature differential curve, (ii) high-temperature side temperature (b value) (℃) at 1 / 10 of the peak top height, (iii) weight loss rate (wt%) at the low-temperature side temperature at 7.5 / 10 of the peak top height, (iv) peak top temperature (℃), and (II) surface modification processability were evaluated. The results are shown in Table 1.
[0056] Comparative Example 2 In Comparative Example 1, except that Ocsial's "Tuball", a single-walled carbon nanotube, was used as an oriented aggregate of fibrous carbon nanostructures, the oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs) was evaluated in the same manner as in Comparative Example 1 for (I) the half-width (°C) of the peak of the temperature differential curve, (ii) the high-temperature side temperature (b value) (°C) at 1 / 10 of the peak top height, (iii) the weight loss rate (wt%) at the low-temperature side temperature at 7.5 / 10 of the peak top height, and (iv) the peak top temperature (°C), as well as (II) surface modification processability. The results are shown in Table 1.
[0057] Comparative Example 3 In Comparative Example 1, except that Signis SG-65i, which is a single-walled carbon nanotube, was used as an oriented aggregate of fibrous carbon nanostructures, the oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs) was evaluated in the same manner as in Comparative Example 1. (I) (i) half-width (°C) of the peak of the temperature differential curve, (ii) high-temperature side temperature at 1 / 10 of the peak top height (b value) (°C), (iii) weight loss rate (wt%) at the low-temperature side temperature at 7.5 / 10 of the peak top height, and (iv) peak top temperature (°C), as well as (II) surface modification processability were evaluated. The results are shown in Table 1.
[0058] Comparative Example 4 In Comparative Example 1, except that "MEIJO eDIPS EC1.5" manufactured by Meijo Nano Carbon Co., Ltd., which is a single-walled carbon nanotube, was used as an oriented aggregate of fibrous carbon nanostructures, the oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs) was evaluated in the same manner as in Comparative Example 1 for (I) (i) half-width (°C) of the peak of the temperature differential curve, (ii) high-temperature side temperature at 1 / 10 of the peak top height (b value) (°C), (iii) weight loss rate (wt%) at the low-temperature side temperature at 7.5 / 10 of the peak top height, and (iv) peak top temperature (°C), as well as (II) surface modification processability. The results are shown in Table 1.
[0059] [Table 1]
[0060] From Table 1, it can be seen that the fibrous carbon nanostructures of Examples 1 to 4 have been better surface modified and have excellent dispersibility (overall evaluation is "excellent") compared to the fibrous carbon nanostructures of Comparative Examples 1 to 4. [Industrial Applicability]
[0061] According to the present invention, it is possible to provide a fibrous carbon nanostructure that is easy to subject to surface modification treatment and a method for producing the same. Furthermore, according to the present invention, it is possible to provide a method for producing a surface-modified fibrous carbon nanostructure which has been satisfactorily surface-modified. [Explanation of symbols]
[0062] T max Peak top temperature (℃) DTG max temperature T max Differential thermogravimetry at (% / ℃) (peak top height h) T ini Peak start temperature (℃) T a Differential thermogravimetry is DTG max Temperature (℃) at which the temperature becomes 1 / 2 (h / 2) (low temperature side) Tb Differential thermogravimetry is DTG max Temperature (℃) at which the temperature becomes 1 / 2 (h / 2) of the b >T a ) T c Differential thermogravimetry is DTG max Temperature (℃) at which the temperature becomes 1 / 10 (h / 10) (high temperature side) T d Differential thermogravimetry is DTG max Temperature (℃) at which the temperature becomes 7.5 / 10 (7.5h / 10) (low temperature side) AT ini From T d Peak area (peak integral value) in the temperature range up to
Claims
1. A method for producing a fibrous carbon nanostructure, comprising the steps of: The fibrous carbon nanostructure to be produced has a half-width of a peak of a temperature differential curve, which is a first differential curve of a thermogravimetric curve obtained by thermogravimetric analysis in a dry air atmosphere, of 38°C or more and less than 90°C, and a high-temperature side temperature at a height that is 1 / 10 of the peak top height of the peak is 658°C or more, and is made of single-walled carbon nanotubes; A method for producing a fibrous carbon nanostructure, comprising the step of heating a raw material, a fibrous carbon nanostructure, to a temperature of 120° C. or higher and 300° C. or lower in a vacuum atmosphere.
2. A method for producing a fibrous carbon nanostructure, comprising the steps of: The fibrous carbon nanostructure to be produced has a half-width of a peak of a temperature differential curve, which is a first differential curve of a thermogravimetric curve obtained by thermogravimetric analysis in a dry air atmosphere, of 38°C or more and less than 90°C, and a high-temperature side temperature at a height that is 1 / 10 of the peak top height of the peak is 658°C or more, and is made of single-walled carbon nanotubes; A method for producing a fibrous carbon nanostructure, comprising the step of heating a raw material, a fibrous carbon nanostructure, to a temperature of 800° C. or higher and 1100° C. or lower in an inert gas atmosphere.
3. A method for producing a fibrous carbon nanostructure as described in claim 1 or 2, wherein the fibrous carbon nanostructure produced has a weight loss rate of 40 weight % or less at a lower temperature at a height that is 7.5 / 10 of the peak top height of the peak.
4. 4. The method for producing a fibrous carbon nanostructure according to claim 1, wherein the produced fibrous carbon nanostructure has a peak top temperature of the peak of 530°C or higher and lower than 730°C.
5. The method includes a step of subjecting a fibrous carbon nanostructure to a surface modification treatment to obtain a surface-modified fibrous carbon nanostructure, The method for producing a surface-modified fibrous carbon nanostructure is characterized in that the half-width of a peak in a temperature differential curve, which is a first derivative curve of a thermogravimetric curve obtained by thermogravimetric analysis in a dry air atmosphere, is 38°C or more and less than 90°C, and the high-temperature side temperature at a height that is 1 / 10 of the peak top height of the peak is 658°C or more, and the fibrous carbon nanostructure is made of single-walled carbon nanotubes.
6. The method for producing a surface-modified fibrous carbon nanostructure according to claim 5 , wherein the surface modification treatment is a wet oxidation treatment.
7. The method for producing a surface-modified fibrous carbon nanostructure according to claim 5 or 6, wherein the fibrous carbon nanostructure has a weight loss rate of 40% or less at a lower temperature at a height that is 7.5 / 10 of the peak top height of the peak.
8. 8. The method for producing a surface-modified fibrous carbon nanostructure according to claim 5, wherein the fibrous carbon nanostructure has a peak top temperature of the peak of 530°C or higher but lower than 730°C.
Citation Information
Patent Citations
Method for refining composition containing carbon nanotube
JP2005097024A
Method for producing carbon nanotube dispersion liquid
JP2013067540A
Carbon nanotube and dispersion liquid thereof, and self-supporting film and composite material
JP2015105212A
Method of purifying carbon nanotubes
JP2018039721A
Carbon nanotube / carbon nanohorn complex, method for producing carbon nanotube / carbon nanohorn complex, and application therefor
WO2012133239A1